The Nestorian fathers - Aprem, Mar, 1940- (Trichur : Mar Narsai Press, 1976)
Biographical sketches of the Nestorians, Syrian Church of the East
Bibliography: p. [163]-164
Keywords: Nestorian Church -- Biography